Development of Functional Architecture and Systems Integration in the Engineering Design Process for the Implementation of New Functions in E-TECH Hybrid Powertrains. Semestre de Industria (2024)
ABSTRACT : This report presents the development of the author's internship that took place at FEV Iberia SL, a Spanish company of German origin that specializes in the provision of engineering services to a number of leading manufacturers of propulsion systems worldwide. The project is primarily concerned with the implementation of services and technical assistance, including PFS (Pilote Fonctions Systême), in the design and development of internal combustion engines, hybrid and electric vehicle propulsion systems. The project specifically focuses on the study of the functional architecture and integration of the S34 (Powertrain Torque Management) and S42 (Hybrid Management) systems in the powertrain of the E-TECH vehicles of the RENAULT-HORSE group. Additionally, it analyzes the impact of these systems in relation to other engine systems and functions established in the vehicle software.  The main objective of these developments is to ensure compliance with international standards in the automotive industry. They are organized around a federative process led by HORSE, which forms the basis of the company's Design System framework. This, in turn, contributes to the efforts to reduce emissions in the market, as well as to the optimization of the systems implemented in the vehicle's power plant, with the goal of ensuring competitiveness and customer satisfaction in the supply of hybrid vehicles that meet the standards proposed by the brand in the coming years.